Polymerizarization of Lactide to PLA: effect of reaction temperature: article / Amira Amiza Aminudin, Norliza Ibrahim and Amira Nadzirah Suhaidi - Aminudin, Amira Amiza; Ibrahim, Norliza; Suhaidi, Amira Nadzirah (2019)
Polylactic acid (PLA) is one of biodegradable polymer produced from sustainable resources and have a few applications in various field. The reaction temperature is one of the factors that can affect the rate of reaction. From previous research, the inconsistent reaction temperature used for polymerization of lactide to PLA makes it difficult to identify which the best reaction temperature. Since the parameter involved is temperature, it is important to determine the value of the rate constant, frequency factor and the activation energy. Objectives of this study are to produce PLA at different temperatures and to characterize the PLA using Fourier transform infrared spectrometer and UV visible spectrophotometer.